Patient and public involvement in health technology assessment: update of a systematic review of international experiences. (5th February 2021) - Gagnon, Marie-Pierre; Tantchou Dipankui, Mylène; Poder, Thomas G.; Payne-Gagnon, Julie; Mbemba, Gisèle; Beretta, Valentina
Abstract: Objective: To summarize current evidence on patient and public involvement (PPI) in health technology assessment (HTA) in order to synthesize the barriers and facilitators, and to propose a framework to assess its impact. Methods: We conducted an update of a systematic review published in 2011 considering the recent scientific literature (qualitative, quantitative, and mixed-methods studies). We searched papers published between March 2009 (end of the initial search) and December 2019 in five databases using specific search strategies. We identified other publications through citation tracking and contacting authors of previous related studies. Reviewers independently selected relevant studies based on prespecified inclusion and exclusion criteria. We extracted information using a pre-established grid. Results: We identified a total of 7872 publications from the main search strategy. Ultimately, thirty-one distinct new studies met the inclusion criteria, whereas seventeen studies were included in the previous systematic review. PPI is realized through two main strategies: (i) patients and public members participate directly in decision-making processes (participation) and (ii) patients or public perspectives are solicited to inform decisions (consultation or indirect participation). This review synthesizes the barriers and facilitators to PPI in HTA, and a framework to assess its impact is proposed. Conclusion: The number of studies on patients or public involvement in HTA has dramatically increased in recent years. Findings from this updated systematic review show that PPI is done mostly through consultation and that direct involvement is less frequent. Several barriers to PPI in HTA exist, notably the lack of information to patients and public about HTA and the lack of guidance and policies to support PPI in HTA.